Social psychology of politics - Crano, William D.; Fiedler, Klaus; Forgas, Joseph P. (Sydney Symposium of social psychology, 2015)
pt. 1. Political attitudes and values -- pt. 2. Political perception and communication -- pt. 3. Social cognition and democracy -- pt. 4. The politics of identity and intergroup relations